Comment on "Optimal centrifugal isolating of liposome–protein complexes from human plasma" by L. Digiacomo, F. Giulimondi, A. L. Capriotti, S. Piovesana, C. M. Montone, R. Z. Chiozzi, A. Laganá, M. Mahmoudi, D. Pozzi and G. Caracciolo, Nanoscale Adv., 2021, 3, 3824. Issue 1 (30th November 2022) - Münter, Rasmus; Simonsen, Jens B.
Abstract : Centrifugation is unsuitable for isolating liposomes from human plasma, and should not be the method of choice for researchers wanting to investigate the protein corona of liposomes for drug delivery. Abstract : In a recent paper in Nanoscale Advances, Digiacomo et al. conclude that centrifugation should be the method of choice for researchers who want to investigate the protein corona of liposomes for drug delivery in human plasma. In this Comment, we however propose the opposite – that centrifugation, in most cases, is unsuitable for isolating liposomes from human plasma. Our conclusion is based on the bulk literature on this and similar topics, and new experimental data based on formulations and protocols like the ones used by Digiacomo et al.